Analytical validation and implementation of a pan cancer next-generation sequencing panel, CANSeqTMKids for molecular profiling of childhood malignancies - Schilter, Kala F.; Smith, Brandon A.; Nie, Qian; Stoll, Kathryn; Felix, Juan C.; Jarzembowski, Jason A.; Reddi, Honey V. (Frontiers in Genetics, 2023)
Next Generation Sequencing (NGS) allows rapid analysis of multiple genes for the detection of clinically actionable variants. This study reports the analytical validation of a targeted pan cancer NGS panel CANSeqTMKids for molecular profiling of childhood malignancies. Analytical validation included DNA and RNA extracted from de-identified clinical specimens including formalin fixed paraffin embedded (FFPE) tissue, bone marrow and whole blood as well as commercially available reference materials. The DNA component of the panel evaluates 130 genes for the detection of single nucleotide variants (SNVs), Insertion and Deletions (INDELs), and 91 genes for fusion variants associated with childhood malignancies. Conditions were optimized to use as low as 20% neoplastic content with 5ng of nucleic acid input. Evaluation of the data determined greater than 99% accuracy, sensitivity, repeatability, and reproducibility. The limit of detection was established to be 5% allele fraction for SNVs and INDELs, 5 copies for gene amplifications and 1100 reads for gene fusions. Assay efficiency was improved by automation of library preparation. In conclusion, the CANSeqTMKids allows for the comprehensive molecular profiling of childhood malignancies from different specimen sources with high quality and fast turnaround time.